Breeding behaviour of wild Whistling Swans - Scott, Dafila (Wildfowl, 1977)
This paper describes a study of the behaviour of wild Whistling Swans Cygnus columbianus columbianus on their breeding grounds on the Yukon-Kuskokwim delta, Alaska, from May to July 1976. There was a separation of roles of male and female parents during incubation: the female was mainly responsible for incubation, the male for defence. This difference largely disappeared after hatching and subsequent parental care was more equally shared. These results are compared with studies on captive pairs. Observations on non-breeding birds and some of the important environmental influences on the swans during the breeding season are described.